A NEW MAPPING OF THE CEPHEID INSTABILITY STRIP - Turner, David G. (Одеські астрономічні публікації, 2017)
Results are presented for a new mapping of the instability strip for Milky Way Cepheids based upon eld reddenings for 40 stars (mainly members of open clusters and associations), color excesses for 53 stars obtained from reddening-independent systems, and photometric reddenings for 200 additional Cepheids tied to the new system. The data provide new insights into features of the Cepheid instability strip and indicate that photometric reddenings for Cepheids are generally not of high accuracy.